2011
DOI: 10.3409/fb59_3-4.183-187
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Blood Chemistry in Broiler Chickens during the Fattening Period

Abstract: The aim of the study was to determine the changes in the selected biochemical serum parameters in male Ross 308 broilers during the fattening period. The birds were kept under standard farm conditions and they were fed on commercial mixtures. The blood for analysis was taken from the jugular vein on the 14 th , 21 st , and 42 nd days of age. The concentration of serum protein (total protein, albumins, uric acid, creatinine), lipid (TG, TCHL, HDL) and mineral (Ca, P i , Mg, Fe) indices were determined. The meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
2
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 19 publications
6
38
2
12
Order By: Relevance
“…Mabelebele The serum parameters at the ages of 42 days were similar between the chicken breeds. However, the serum total protein was higher in indigenous Venda than in Ross 308 broiler chickens, the levels reported in the current study were still lower (20 g/L for Ross 308 and 25g/L for indigenous Venda chickens) than those reported (33-47g/L in Ross 308 broiler aged 42 days) in a study by Piotrowska et al (2011). Total serum protein can extremely vary in chickens and its variation depends on internal and external factors and results from physiological roles in blood proteins.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Mabelebele The serum parameters at the ages of 42 days were similar between the chicken breeds. However, the serum total protein was higher in indigenous Venda than in Ross 308 broiler chickens, the levels reported in the current study were still lower (20 g/L for Ross 308 and 25g/L for indigenous Venda chickens) than those reported (33-47g/L in Ross 308 broiler aged 42 days) in a study by Piotrowska et al (2011). Total serum protein can extremely vary in chickens and its variation depends on internal and external factors and results from physiological roles in blood proteins.…”
Section: Discussioncontrasting
confidence: 83%
“…Other differences identified where serum creatinine was higher for Ross 308 broiler than indigenous Venda chickens at 42 and 90 days of age. Serum creatinine is an important indicator of protein metabolism, a by-product of phosphocreatine breakdown in skeletal muscles (Piotrowska et al, 2011). Its concentration is directly related to muscle mass and is associated with age and physical activity (Szabo et Minerals are essential for chickens' growth and are involved in many biosynthetic processes in the body.…”
Section: Discussionmentioning
confidence: 99%
“…An important factor in the efficacy of feed additives in animal nutrition is the course of metabolic processes, which is manifested in, among other things, changes in the values of biochemical and hematological markers (30). Blood analyses, widely used in large domestic animal medicine, are not commonly performed in avian diagnostics, because no physiological reference values are available (28). Furthermore, the considerable individual differences in the biochemical indices of birds are the main reason for the wide physiological ranges specified for chickens (17).…”
Section: Resultsmentioning
confidence: 99%
“…Lipid metabolites are strongly associated with energy metabolism and reflect its fluctuation during the growth period (28). Numerous studies on humans and animals showed that dietary fructans have hypolipidemic properties manifested by a lowered plasma total cholesterol and triacylglycerol content (18,50).…”
Section: Tab 3 Effect Of the Dietary Level Of Two Types Of Inulin (mentioning
confidence: 99%
“…A elevação dos níveis de GGT e AST, podem indicar problemas metabólicos no fígado, entretanto AST não é alterada somente em casos de lesão hepática, a alteração em seus níveis também pode ser devido a lesões musculares o que pode ser comprovado quando também ocorre aumento concomitante da creatinina quinase (CK) (Traesel et al 2011). Os níveis séricos de TGL nos frangos de corte sofrem um decrésci-mo normal a partir da segunda semana de vida das aves (Piotrowska et al 2011), entretanto a alimentação também pode afetar esses níveis como demonstrado nos estudos de Manan et al (2012) No Experimento II o uso de farinha de carne, classificando essa dieta como dieta de baixa digestibilidade, pode explicar a maior variação dos parâmetros estudados em comparação com os resultados obtidos para os mesmos parâmetros no experimento I, onde não foram observadas tantas variações (Lee et al 2004). A utilização de dietas altamente digestíveis dificulta a detecção de aumento da digestibilidade, quando proporcionada pela inclusão de aditivos melhoradores de desempenho.…”
Section: Quadro 2 Descrição Dos Tratamentos De Acordo Com a Porção Vunclassified